NF-kappa B signaling modulation by EBV and KSHV - Oliveira, Deilson Elgui de [UNESP]; Ballon, Gianna; Cesarman, Ethel (Elsevier B.V. London, 2010)
The nuclear factor (NF)-kappa B signaling pathway is pivotal for immune system function. Not surprisingly, pathogenic microorganisms have developed strategies to subvert it. Two examples are Epstein-Barr virus (EBV) and Kaposi sarcoma herpesvirus (KSHV), oncogenic gamma-herpesviruses that establish a lifelong latent infection in their human hosts. The modulation of NF-kappa B signaling by EBV and KSHV is not only important for viral infection, but also contributes to the development of malignant neoplasia. This review explores the current knowledge of NF-kappa B modulation by EBV and KSHV, focusing on connections between viral biology and human carcinogenesis.